Challenges in the Etiology and Diagnosis of Acute Febrile Illness in Children in Low- and Middle-Income Countries. (7th April 2016) - Iroh Tam, Pui-Ying; Obaro, Stephen K.; Storch, Gregory
Abstract: Acute febrile illness is a common cause of hospital admission, and its associated infectious causes contribute to substantial morbidity and death among children worldwide, especially in low- and middle-income countries. Declining transmission of malaria in many regions, combined with the increasing use of rapid diagnostic tests for malaria, has led to the increasing recognition of leptospirosis, rickettsioses, respiratory viruses, and arboviruses as etiologic agents of fevers. However, clinical discrimination between these etiologies can be difficult. Overtreatment with antimalarial drugs is common, even in the setting of a negative test result, as is overtreatment with empiric antibacterial drugs. Viral etiologies remain underrecognized and poorly investigated. More-sensitive diagnostics have led to additional dilemmas in discriminating whether a positive test result reflects a causative pathogen. Here, we review and summarize the current epidemiology and focus particularly on children and the challenges for future research.